The storm - McNeill, Elisabeth (Oxford , Canelo, 2021)
When Scottish village is struck by grief those left behind must help one another find hope. It is 1881, and when a violent storm devastates the Scottish fishing village of Eyemouth few families escape unscathed. Newly wed Rosabelle Maltman loses her husband, and her mother-in-law Effie lost her husband and three sons. For these women and their neighbours in the close-knit community life will never be the same again
A level O level
Keywords: Novel